Auralisation of the Transition between Coupled Rooms - McKenzie, Thomas; Schlecht, Sebastian J.; Pulkki, Ville (2021 Immersive and 3D Audio: From Architecture to Automotive, I3DA 2021, 2021)
The perceptual experience of the transition between coupled rooms remains a little investigated area of research. This paper presents a pipeline for auralising the transition between coupled rooms, utilising a time-varying partitioned convolution for fast position-dependent switching between spatial room impulse responses (SRIRs) and parametric binaural rendering over highly acoustically transparent headphones, with in-situ calibration to the corresponding real-world acoustics. The system is verified by an in-situ listening test with both real and virtual stimuli, conducted in six degrees-of-freedom virtual reality with three-dimensional visuals from measured room models. Results show that the auralisation is rated as highly natural, equalling the naturalness of the corresponding real world auditory stimuli. This pipeline is therefore appropriate for testing of coupled room transition algorithms and SRIR interpolation techniques, as well as non-in-situ testing.
CRIS-Team Scopus Importer:2023-11-06
Keywords: Coupled rooms; Room transition; Six degrees-of-freedom; Spatial room impulse response